Endosteal and periosteal blood flow quantified with dynamic contrast-enhanced fluorescence to guide open orthopaedic surgery - Jiang, Shudong (Proc SPIE Int Soc Opt Eng, 2020)
Due to the lack of objectively measurable or quantifiable methods to assess the bone perfusion, the success of removing devitalized bone is based almost entirely on surgeon’s experience and varies widely across surgeons and centers. In this study, an indocyanine green (ICG)-based dynamic contrast-enhanced fluorescence imaging (DCE-FI) has been developed to objectively assess bone perfusion and guide surgical debridement. A porcine trauma model (n = 6 pigs × 2 legs) with up to 5 conditions of severity in loss of flow in each, was imaged by a commercial fluorescence imaging system. By applying the bone-specific hybrid plug-compartment (HyPC) kinetic model to four-minute video sequences, the perfusion-related metrics, such as peak intensity, total bone blood flow (TBBF) and endosteal bone blood flow to TBBF fraction (EFF) were calculated. The results shown that the combination of TBBF and EFF can effectively differentiate injured from normal bone with the accuracy, sensitivity and specificity of 89%, 88% and 90%, respectively. Our subsequent first in human bone blood flow imaging study confirmed DCE-FI can be successfully translated into human orthopaedic trauma patients.